Effect of Tagetes Erecta L. Leaf Extract with Ethanol and Water Solution on Behavior Mosquito Larvae Culex Sp. - Aida safriani; Devi Syafrianti; Safrida Safrida; Supriatno Supriatno; Hafnati Rahmatan (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2023)
ABSTRACTMosquitoes Culex sp. become a vector for transmitting filariasis. Prevention efforts are carried out by controllingathe presenceoof Culex sp. mosquito larvae. in nature. The purpose of thisastudyewas to determine the effect of Tagetes erecta L. leaf aextract with ethanol and awateri asl solventa on the behavior of Culex sp. mosquito larvae. Thei researchi method used in this study wasiexperimental method with a complete randomized design (CRD) factorial consisting of from factor A (type of solvent) 2 levels and factor B (type of concentration) 6 levels including negative control and positive control so that 12 treatment combinations with 3 replications were obtained. The object used in this study was the Culex sp. mosquito larvae. instar 3 of 360 individuals treated with various concentrations of Tagetes erecta L. leaf extract accompanied by positive and negative controls. The results of observing the behavior of the larvae showed the movement of the larvae from active to inactive with a position at the bottom of the container. The conclusion of this study is that the behavior of the larvae during exposure shows a decreasei in the intensityi of movement with the position of the larvaei ati the bottom ofi the icontainer.Keyword: Tagetes erecta L., Culex sp. larvae, behaviorABSTRAKNyamuk Culex sp. menjadi vektor penular penyakit filariasis. Upaya pencegahan dilakukan dengan mengendalikanakeberadaan larva nyamuk Culex sp. di alam. Tujuan penelitian ini untuk mengetahui pengaruh pemberian ekstrak daun Tagetes erecta L. dengan pelarut etanol dan air terhadap tingkah laku larva nyamuk Culex sp.. Metode penelitian yang digunakan pada penelitian ini adalah metode eksperimen dengan rancangan penelitian adalahaRancangan Acak Lengkap (RAL) Faktorial yang terdiri dari faktor A (jenis pelarut) 2 taraf dan faktor B (jenis konsentrasi) 6 taraf termasuk kontrol negatif dan kontrol positif sehingga didapatkan 12 kombinasi perlakuan dengan 3 ulangan. Objek yang digunakan adalahalarva nyamuk Culex sp. instar 3 sebanyak 360 ekor yang diberikan perlakuan danaberbagai konsentrasi ekstrak daun Tagetes erecta L. disertai kontrol positif dan kontrol negatif. Hasil penelitian pengamatan tingkah laku larva menunjukkan pergerakan larva dari aktif menjadi tidak aktif dengan posisi berada di dasar wadah. Simpulan dari penelitian ini adalah tingkah laku larva saat pemaparan menunjukkan penurunan intensitas gerakan dengan posisi larva berada di dasar wadah.Kata kunci: Tagetes erecta L., larva Culex sp., tingkah laku